Genes Associated With Chromatin Modification Within the Swine Placenta Are Differentially Expressed Due to Factors Associated With Season - Rempel, Lea A.; Parrish, John J.; Miles, Jeremy R. (Frontiers in Genetics, 2020)
Seasonal reproductive inefficiency is still observed in modern swine facilities. We previously reported global placental methylation activity was reduced from summer breedings and tended to be less from semen collected during cooler periods. The objective of the current study was to evaluate chromatin modification marks within swine placenta in relationship to breeding season, semen collection season, and semen storage. White composite gilts were artificially inseminated in August or January using single-sire semen that was collected during warm or cool periods and stored as either cryopreserved or cooled-extended. Gilts were harvested 45 d post-breeding and placental samples from the smallest, average, and largest fetus in each litter were collected and stored at -80C until RNA extraction. An RT2 Profiler assay featuring 84 known chromatin modification enzyme targets was performed using placental RNA pooled by litter. Real-time quantitative PCR results were analyzed using the MIXED procedure and p-values were Hochberg corrected using the MULTTEST procedure in SAS. The complete model included the fixed effects of: breeding season (winter or summer), semen collection season (cool or warm), semen storage (cooled-extended or cryopreserved), interactions; boar as repeated effect; and plate as random effect. If interactions were not significant, only main effects were tested. The genes; ATF2, AURKA, and KDM5B were different (P<0.05) by interaction of breeding season, semen collection season, and semen storage. In general, the greatest (P<0.05) expression was in placentas derived from summer breedings. Expression of AURKA was also influenced by semen collection and storage. Expression of placental KDM5B from winter breedings was also greater (P<0.05) from semen collected during cool periods. Placental expression of: ASH2L, DNMT3B, ESCO1, HDAC2, ING3, KDM6B, MYSM1, and SMYD3 were greater (P<0.05) from summer breedings. Increased expression of known chromatin modification genes, from placentas derived from summer breedings, are likely responsible for differences in gene transcription between summer- or winter-derived placentas.